Has intergenerational progress stalled? Income growth over five generations of Americans - Kevin Corinth; Jeff Larrimore (American Enterprise Institute (AEI), 2024)
We find that each of the past four generations of Americans was better off than the previous one, using a post-tax, post-transfer income measure constructed annually from 1963-2022 based on the Current Population Survey Annual Social and Economic Supplement. At age 36-40, Millennials had a real median household income that was 18 percent higher than that of the previous generation at the same age. This rate of intergenerational progress was slower than that experienced by the Silent Generation (34 percent) and Baby Boomers (27 percent), but similar to that experienced by Generation X (16 percent). Slower progress for Generation X and Millennials is due to their stalled growth in work hours-holding work hours constant, they experienced a greater intergenerational increase in real market income than Baby Boomers. Intergenerational progress for Millennials under age 30 has remained robust as well, although their income growth largely results from higher reliance on their parents. We also find that the higher educational costs incurred by younger generations is far outweighed by their lifetime income gains.
Keywords: D31; E24; H24; J3; J62; 330; Full income; Growth; Generations; Mobility; Millennials